Stress and Deformation Behavior of 2D Composite Cellular Actuator Structures of Ceramic Building Blocks and Epoxy Resins. Issue 9 (31st March 2022) - Eichhorn, Franziska; Schiegerl, Helmut; Köllner, David; Kakimoto, Ken-ichi; Fey, Tobias
Abstract : 2D actuator composite structures are fabricated of lead zirconate titanate (PZT) and Al2 O3 building blocks with an epoxy resin matrix. This novel modular concept gives the possibility to create complex geometric structures where the structure itself tailors the physical properties. To improve the possibilities of excitation or loading and determine the influence of the geometric parameters as slenderness ratio t 2 · g −1 and active area A active finite element (FE) simulations are used. The stress distribution σ yy within the unit cell and the resulting strain amplification a y are tested with different mechanically coupled thermal excitation modes. A homogeneous excitation of the PZT building blocks and a maximum A active of 24% led to a maximum of strain amplification and a reduction of induced tensile stresses. In addition, zero deformation could be generated by modifying the structure design with a slenderness ratio of 0.5. Further geometric variations offer the potential to increase the strain amplification. Abstract : The influence of active area A active and slenderness t 2 · g −1 for cellular composite structures on strain amplification a y and stress distribution σ yy is investigated with finite‐element simulations. Different mechanically coupled thermal excitations of the 2D modular cellular composite structures of Al2 O3 and lead zirconate titanate (PZT) are analyzed. By increasing t 2 · g − 1, the strain amplification a y increases until saturation.